Economic evaluation of bank exit regimes in US, EU and Japanese financial centres - Peik Granlund (Bank of Finland, 2003)
This paper evaluates bank exit regimes in selected financial centres using econometric methods.The focus is on bank exit regimes applicable to commercial banks in New York, London, Frankfurt, Helsinki and Tokyo in 1998-2002.Bank exit regimes are studied from the perspective of bank creditors and bank shareholders.In order to apply econometric methods, the exit regimes are indexed and then evaluated by comparing them with market indicators that reflect the interests of bank creditors and shareholders.These market indicators comprise bank refinancing costs and bank growth rates.In other words, two specific questions are addressed: (1) Do differences in bank exit regimes of significance to bank creditors explain differences in bank refinancing costs?(2) Do differences in bank exit regimes significant to bank shareholders explain differences in bank growth?The study shows that in those financial centres where the probability of bailout is higher, refinancing costs for banks are lower.
URN:NBN:fi:bof-20140807242
Keywords: 330